Biotechnology for developing countries in developing countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Luxembourg from June 26 to 30 1989 symposium on 'Plant Biotechnologies for Developing Countries' organized by CTA with FAO